PENERAPAN DESAIN SISTEM PEMBELAJARAN ASSURE UNTUK MENINGKATKAN HASIL BELAJAR MEMUKUL BOLA DALAM PERMAINAN KASTI PADA SISWA KELAS IV SD NEGERI PURWOREJO KECAMATAN BANJARSARISURAKARTA TAHUN PELAJARAN 2011/201 - Khasanah, Dewi Indah Nur (Jurnal Phederal Penjas, 2013)
The purposeof this studywas to determinethe effectiveness ofthe implementation oflearning systemsdesignASSUREtoimprove learning outcomesin the game ofbaseballto hit the ballinthe fourth gradeelementary schoolstudentsPurworejoBanjarsariSurakartadistrictin the school year2011/2012.This study usesclassroom Action ResearchorClassroomActionResearch.The experiment was conductedin two cycles, eachcycleconsisting offourphases: planning, action, observationand reflection. Subjectsin this study weregrade IVElementary SchoolDistrictPurworejoBanjarsariSurakartaacademic year2011/2012, amounting to 30 studentsconsistingof 16boys and14girlsstudents. Data sourcesare fromteachers and students. The data collection techniqueis totestandobservation. The validity ofdata usingtriangulationstechniquemethods. The data wereobtained throughobservationsby researchersand collaboratorsduring the learning processtakes place. The datais the result ofstudent learningin hitting the ballobtainedthroughobservation sheetscoveringthe cognitive,the affectiveandpsychomotordomains. Data analysisin this study useda comparative descriptiveanalysisusingpercentagetechniquetoseetrendsin learning activities.Based on the resultsobtainedthe conclusionthat:1)the application ofsystems designASSURElearningcan improvelearning outcomesto hit the ballinthe fourth gradeelementary schoolstudentsPurworejoDistrictBanjarsariSurakarta, wherelearning outcomesprasiklusthefirst cycleand fromcycle I tocycle IIobtaineda significant improvementthatstudents who passtheprasiklusare11 studentsor 36, 67%later in thecycle increasedthecompletecategoryis 16or 53students, 33%, and on the second cycleincreased to25 studentsor83.33%. 2)Most of thestudents agreedwith the implementation oflearning systemsdesignASSURE.The conclusion of this study show that the implementation design of ASSURE learning system can improve student baseball striking achievement of SDN Purworejo Grade IV Banjarsari, Surakarta, and Academic Year 2011/2012.Keywords:strike ball, baseball, ASSURE learning system design